The Stigm and Communication Pattern of Radical-Labelled Group Communication in Bengkulu - Alfarabi Alfarabi; Panji Suminar (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2021)
Bengkulu Province is an area that according to a survey by the National Counterterrorism Agency (BNPT) in 2017 has the highest potential for radicalism in Indonesia. The BNPT data is quite surprising because Bengkulu province has never been recorded as a place of radicalism and terrorism. This research explores the causes of religious groups that are considered radical in Bengkulu province. The method used in this research is qualitative with a case study approach. The results of the study provide the fact that there is a growing discourse in society that creates the image of SS s as a radical group in North Bengkulu and Rejang Lebong districts. The SS label as a group that adheres to radicalism can be explained from two perspectives. First, from the internal side, this group lives exclusively and does not interact intensely with the surrounding community. This exclusive life makes the perspectives, attitudes and behavior of SS group members differ from those of society. Differences in viewpoints, attitudes and actions become the embryo for conflicts with the surrounding community, especially in terms of beliefs. Meanwhile, from the second point of view, the surrounding community has also labeled the SS group as adherents of radicalism without knowing what the meaning and limitations of radicalism itself are. The role of the mass media in reporting on radical groups with several easily recognizable symbols such as robes, veils and beards also influences people's perceptions of the SS groups around them. This condition was further strengthened by the labeling carried out by several religious and community leaders who were used as references to portray SS groups. The label and image of radicalism in the end make the SS group's relationship with the surrounding community social distancing and foster stereotypes and prejudice. Keywords: exclusivity, label, prejudice, radicalism, Bengkulu